STUDENTS’ PERCEPTION ON INTERNET USE SOURCES TO SUPPORT WRITING THESIS AND ITS CORRELATION WITH THESIS QUALITY - Sirrul Bari (Language-Edu, 2020)
The present study aimed to uncover the perception of the students on internet use as reference to support thesis writing and correlation between internet use Sources and Thesis Quality Score. In this study, the researcher used a design measured suitable that is quantitative, because the study focused to determine correlation between student’s perception and thesis quality. It means that the researcher illustrated all phenomenon that occur from the object of the research literally, truly by statistic method. Sixty students were employed and the instrument in this study was rating scale with questionnaire. The first questionnaire integrated 24 items used to know students perception on internet use. The second questionnaire contains 1 item questionnaire. The findings showed that there was no any significant correlation between perception and thesis quality. The perception of students on internet use as reference was good (68,3%). Then, thesis quality score of the students, it was revealed that 37 students (63, 8%) of 60 students. And the percentage p=0.973 showed students perception on internet use did not relate with thesis quality. And the Pearson correlation 0.004 showed there is no any correlation. The significant numerical data (p=0.973>a=0.05) with the result that H1 rejected (H0 accepted).